2017
DOI: 10.1016/j.athoracsur.2017.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Anomalies in Patients With Transposition of the Great Arteries and Their Impact on Postoperative Outcomes

Abstract: With the exception of patients whose circumflex artery branches off of the right coronary artery, an anomaly that clearly has no effect on postoperative follow-up, patients with unusual coronary patterns are at higher risk for adverse postoperative outcomes than patients with normal coronary anatomy and must be monitored carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 16 publications
(28 reference statements)
0
45
0
Order By: Relevance
“…Anomalous coronary arteries are common in patients undergoing the ASO, making up approximately one-third of children operated [6,38,39]. The most common variant of coronary anatomy pattern is the left anterior descending artery arising from sinus 1 and right coronary and left circumflex coronary arteries arising from sinus 2 [6,12,38,39].…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous coronary arteries are common in patients undergoing the ASO, making up approximately one-third of children operated [6,38,39]. The most common variant of coronary anatomy pattern is the left anterior descending artery arising from sinus 1 and right coronary and left circumflex coronary arteries arising from sinus 2 [6,12,38,39].…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%
“…There are conflicting data in the literature on whether abnormal coronary artery pattern is a risk factor for death [6,[38][39][40][41][42][43][44][45][46][47][48]. The meta-analysis by Pasquali and colleagues [41] of 1942 patients reported that any variant of coronary artery anatomy doubled the risk of death compared with normal coronary anatomy.…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%
“…Large studies from the 1980s and 1990s described a greater mortality for patients with single and intramural coronaries. 4,5 Despite some recent studies still showing a greater mortality in patients with a single coronary, 6 others have concluded that coronary abnormalities are no longer a risk factor for mortality, 7 presumably due to increased surgical experience.…”
mentioning
confidence: 99%
“…
The article by Moll and colleagues [1] reports the results of a retrospective review of 715 patients undergoing arterial switch operation at their institution over a 26-year period. The main stated findings of the article were that:(1) complex coronary anomalies (CCAs) have an important influence on the reintervention rate and the postoperative coronary event rate among their patients; (2) a common variant, circumflex coronary artery (Cx) from the right coronary artery (1LAD2RCALCx), does not appear to have an effect on the clinical outcomes studied; and (3) complex cardiac anomalies, which were included in the population, were a risk factor for worse outcome.There are two integrated messages from their article, the first of which is unstated directly: that the trap-door technique could mitigate the effects of some of these anomalies.
…”
mentioning
confidence: 99%
“…The article by Moll and colleagues [1] reports the results of a retrospective review of 715 patients undergoing arterial switch operation at their institution over a 26-year period. The main stated findings of the article were that:…”
mentioning
confidence: 99%